INCREASING THE MICRONUTRIENTS QUALITIES OF FRESH VEGETABLES USING AGRONOMIC MANAGEMENT - Petra Ajiri, Okole (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Several disparate studies have identified vegetables as an essential part of plants that contributes immensely to health and well-being, and they are both provitamins A sources. Improved yields are critical for improving food availability and income generation, which can be used to purchase more food and expand diet diversity. The improved nutrient content is essential for households' nutrition access and availability. As established in the literature, micronutrients are critical for improving health. The present study aimed to examine the effect of agronomic treatment on the micronutrients of vegetables. The result indicated that IRWH revealed the best-performing agronomical approach to improving yields for vegetables. This is significant because many households prefer vegetables daily as green leafy vegetables.